CircFOXO3 upregulation mediates the radioresistance of glioblastoma by affecting cellular metabolome - Xu, Hao; Xing, Jin; Cheng, Lilin; Wang, Zhihan; Zhao, Liang; Ren, Li; Zhang, Shuai (Frontiers in Pharmacology, 2024)
Introduction Radioresistance remains a significant challenge in the treatment of glioblastoma multiforme (GBM), the most prevalent and lethal brain cancer in adults. Metabolic alterations are known to contribute to radioresistance by activating antioxidant responses and promoting DNA repair. However, the role of circular RNAs in this process, particularly circFOXO3, is not well understood. Methods In this study, we investigated the expression of circFOXO3 in glioma cells exposed to radiation and in recurrent GBM tissues. We performed knockdown and overexpression experiments in vitro and in vivo to assess the effects of circFOXO3 on radiosensitivity. Metabolomic profiling was conducted to explore the metabolic changes associated with circFOXO3 overexpression following irradiation. Results Our results showed significant upregulation of circFOXO3 in glioma cells upon radiation exposure and in recurrent GBM tissues. Knockdown of circFOXO3 increased radiosensitivity both in vitro and in vivo, whereas overexpression of circFOXO3 attenuated radiosensitivity. Metabolomic analysis revealed substantial alterations in lipid and organic compound profiles between circFOXO3-overexpressing and control groups. Additionally, circFOXO3 suppression increased proapoptotic protein levels (Caspase 7 and Bax) and decreased anti-apoptotic protein Bcl-2 levels following radiotherapy. Discussion These findings demonstrate the pivotal role of circFOXO3 in promoting tumor radioresistance through metabolic modulation, suggesting that circFOXO3 could serve as a potential diagnostic and therapeutic target for GBM.